Partisipasi Masyarakat Dalam Pengelolaan Sampah Berbasis Sumber di Desa Baktiseraga Kabupaten Buleleng - Ida Ayu Alit Laksmiwati; I Nyoman Suarsana; Ida Bagus Oka Wedasantara (Bumi Lestari Journal of Environment, 2023)
Community participation determines the success of source-based waste management in Baktiseraga Village, which is waste management carried out in the village itself, so that no more waste is sent to the landfill. TPS 3R supports the sustainability of waste management that has been formed as many as 13 household waste collection networks to convey to the community to start sorting waste both organic and inorganic. This research uses qualitative methods, through data collection techniques with observation (participatory observation) and interviews (indept interviews), document studies and literature studies. To produce a thick description, interpretative descriptive analysis is used, which describes community participation regarding source-based waste management, through the implementation of the TPS 3R program. The purpose of this study was to determine, identify, understand and reveal community participation in source-based waste management, through the implementation of the reduce-reuse-recycle waste management site (TPS 3R) in Baktiseraga Village, District / Buleleng Regency. This research shows that the implementation of TPS 3R in Baktiseraga Village is an effort made to support the sustainability of waste management that has previously been formed. There are thirteen networks of household waste collectors formed to convey to the community to be able to sort organic and inorganic waste independently.